2011
DOI: 10.1124/jpet.111.185769
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Sympatholytic Actions at β-Adrenoceptors Account for the Ocular Hypotensive Actions of Cannabinoid Receptor Agonists

Abstract: Intraocular pressure (IOP) is the primary risk factor for glaucoma, a blinding eye disease. Cannabinoid agonists have long been known to decrease IOP, suggesting they may be useful in glaucoma treatment. However, the specific mechanism by which cannabinoids generate this ocular hypotensive effect remains unknown. The current evidence suggests the cannabinoids reduce IOP through actions at cannabinoid 1 (CB 1 ) receptors within the eye, and adrenergic receptors (ARs) may also contribute to this action of cannab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 38 publications
2
47
0
Order By: Relevance
“…We previously reported that this diurnal variation in IOP persists in CB 1 , CB 2 , and GPR55 knockout animals, indicating that these receptors are not involved. 9,10 Several of the candidate molecules have been linked to GPR119 or GPR18: GPR119 may be a target for N -oleoyl ethanolamine (OEA) and N -palmitoyl ethanolamine (PEA), 35 whereas GPR18 has been proposed as the endogenous partner for NAGly. Notably, activation of GPR18 by NAGly lowers IOP in the eye.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that this diurnal variation in IOP persists in CB 1 , CB 2 , and GPR55 knockout animals, indicating that these receptors are not involved. 9,10 Several of the candidate molecules have been linked to GPR119 or GPR18: GPR119 may be a target for N -oleoyl ethanolamine (OEA) and N -palmitoyl ethanolamine (PEA), 35 whereas GPR18 has been proposed as the endogenous partner for NAGly. Notably, activation of GPR18 by NAGly lowers IOP in the eye.…”
Section: Resultsmentioning
confidence: 99%
“…9,10 More recently, we reported that activation of GPR18 also lowers IOP and that the receptors are present in multiple tissues in the anterior eye. 10 GPR18 is a lipid receptor that is activated by a metabolite of endocannabinoids as described in greater detail below.…”
mentioning
confidence: 97%
“…The ocular hypotensive properties of cannabinoids are dependent on the β -adrenergic receptors stimulation. The cannabinoids reduce IOP by acting as indirect sympatholytics [126]. Cannabinoids can induce COX-2 expression, resulting in higher levels of PGE2 and MMPs, which modulates aqueous outflow resistance [127].…”
Section: Resultsmentioning
confidence: 99%
“…Although the increase was modest, this suggests that MBX2982 has a second target that is coupled to an increase in pressure, not unlike our findings for WIN55212 and CB 1 . 29 The other two compounds may have suffered from limited penetration of the cornea, an issue we encountered for MAGL blockers. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Women are not at greater risk of open angle glaucoma. Women outnumber men in cases of glaucoma (although likely substantially because women outlive men 30 ), meaning that there is a greater need for glaucoma medication among women than men, and the longevity of women leaves them at greater risk of developing tolerance to one or more of the available drugs.…”
Section: Discussionmentioning
confidence: 99%